Social Capital and the Spread of COVID-19: Insights from European Countries - Alina Kristin Bartscher; Sebastian Seitz; Sebastian Siegloch; Michaela Slotwinski; Nils Wehrhöfer (Institute of Labor Economics (IZA), 2020)
We explore the role of social capital in the spread of the recent Covid-19 pandemic in independent analyses for Austria, Germany, Italy, the Netherlands, Sweden, Switzerland and the UK. Exploiting within-country variation, we show that a one standard deviation increase in social capital leads to 12% and 32% fewer Covid-19 cases per capita accumulated from mid-March until mid-May. Using Italy as a case study, we find that high-social-capital areas exhibit lower excess mortality and a decline in mobility. Our results have important implications for the design of local containment policies in future waves of the pandemic.
Keywords: D04; A13; D91; H11; H12; I10; I18; 330; COVID-19; social capital; collective action; health costs; Europe